Study on characteristics of travel insurance plan between AXA Affin Insurance and ACE Synergy Insurance in Anika Insurance Broker Sdn Bhd / Nurul Hazren Mohd Hashim - Mohd Hashim, Nurul Hazren (2011)
Travel insurance is unique insurance product. It provides cover for medical care and travel inconvenient. However, many had not realized the benefit of buying this type of protection while travelling. Basically, this study in on characteristic of travel insurance between Axa Affin General Insurance and Ace Synergy Insurance at Anika Insurance Broker. This study aims to improve the quality of travel insurance and help broker in making their decision. It also wants to improve the quality of service, premium and the insurance itself. In order to conduct this study, data need to be gain from Anika Insurance Brokers Sdn Bhd. They had manages to provide related data such as the travel policy, marketing material from insurer and other information. Company practice will be compared with theory of travel insurance and all difference will be study. These studies also want to minimize the gaps between two insurers by providing few recommendations